RECOMMENDATIONS FOR IMPROVEMENT AND CONTROL MECHANISMS IN THE PRODUCTION PROCESS OF NOXONE 297 SL 1 LITER WITH FMEA APPROACH - Dimas Indra Laksmana; Setio, Hadi Rachmad; Julianus Hutabarat (Journal of Sustainable Technology and Applied Science (JSTAS), 2022)
Product packaging is one of the critical factors in a product. The main problem with product packaging is the frequent occurrence of defects that exceed the company's targets and cause consumer disappointment. The purpose of this research is to minimise the occurrence of defects in product packaging so that recommendations for improvement and performance control mechanisms are needed. Improvement recommendations are made based on analysing the failure mode using the Pareto chart and FMEA (failure mode and effect analysis) tools. The results of this study are in the form of SOP recommendations for improvement and control mechanisms for 3 product packaging.